Successful sulfonylurea treatment in a patient with permanent neonatal diabetes mellitus with a novel mutation - Sung Yeon Ahn; Gu-Hwan Kim; Han-Wook Yoo (Korean Pediatric Society, 2015)
Permanent neonatal diabetes mellitus refers to diabetes that occurs before the age of 6 months and persists through life. It is a rare disorder affecting one in 0.2-0.5 million live births. Mutations in the gene KCNJ11, encoding the subunit Kir6.2, and ABCC8, encoding SUR1 of the ATP-sensitive potassium (KATP) channel, are the most common causes of permanent neonatal diabetes mellitus. Sulfonylureas close the KATP channel and increase insulin secretion. KCNJ11 and ABCC8 mutations have important therapeutic implications because sulfonylurea therapy can be effective in treating patients with mutations in the potassium channel subunits. The mutation type, the presence of neurological features, and the duration of diabetes are known to be the major factors affecting the treatment outcome after switching to sulfonylurea therapy. More than 30 mutations in the KCNJ11 gene have been identified. Here, we present our experience with a patient carrying a novel p.H186D heterozygous mutation in the KCNJ11 gene who was successfully treated with oral sulfonylurea.